Catalytic Reversible (De)hydrogenation To Rotate a Chemically Fueled Molecular Switch. (15th November 2022) - Olivieri, Enzo; Shao, Na; Rosas, Roselyne; Naubron, Jean‐Valère; Quintard, Adrien
Abstract: We report here the development of a rotating molecular switch based on metal‐catalyzed reversible (de)‐hydrogenation. Under an argon atmosphere, acceptorless dehydrogenation induces a switch from an alcohol to a ketone, while reversing to a hydrogen pressure switches back the system to the alcohol. Based on a tolane scaffold, such reversible (de)‐hydrogenation enables 180° rotation. The absence of waste accumulation in a switch relying on chemical stimuli is of great significance and could potentially be applied to the design of efficient complex molecular machines. Abstract : Most chemically fueled molecular switches suffer from the problem of waste accumulation inhibiting the system. Herein, we present a 180° rotating molecular switch based on reversible (de)hydrogenation avoiding waste accumulation. Catalyzed by an iridium complex, switching from a pressure of argon to a pressure of hydrogen triggers a reversible change in the system from alcohol to ketone, promoting the rotation around an alkyne axis.